RELATIVE EFFECTIVENESS OF FINANCIAL INCLUSION, TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING ON WOMEN ENTREPRENEURSHIP DEVELOPMENT IN SELECTED AFRICA COUNTRIES - Bamidele Comfort Olaitan; Kolade Akinpelu Ayobami; REMI-AWOREMI, F. I. (Fuoye Journal of Management, Innovation and Entrepreneurship., 2024)
The relevance of financial inclusion (FI) and technical and vocational education and training (TVET) on women's entrepreneurship development, particularly in Africa, has never been doubted. This was because, with adequate financial inclusion and essential technical and vocational education and training, the capacity of the women to get access to funds and ideas needed to grow their businesses and reshape their business skills had been enhanced. Thus, this study examined the influence of financial inclusion and technical and vocational training on women's entrepreneurship development. To investigate the objective, a panel regression analysis with a random effect test was used. A purposive sampling technique of five African countries was used for the study. With the help of an ex-post facto research design, secondary sources of data were obtained for the study. The result of the panel regression showed that the financial inclusion variable of the financial institution account holders and technical and vocational education and training were significant and positively related to women's entrepreneurship development. The study concluded that financial inclusion and technical and vocational education and training contributed positively to women's entrepreneurship development in the selected African countries.
Keywords: Financial Inclusion; Technical; Vocational; Education Training; Entrepreneurship; Women